APLIKASI PANDUAN GIZI MAKANAN BALITA BERBASIS ANDROID - Yunita Rahma; Dini Suhartini; Sufiatul Maryana (Universitas Teknokrat Indonesia, 2022)
Fulfillment of rich nutrition for toddlers is something that needs to be considered in maintaining health because the age of toddlers enters a nutritional sensitive period. The impact of malnutrition in the first 1000 days of life starting from the fetus to the child is two years old, it not only affects physical development, but also affects subsequent cognitive development, which in turn affects the intelligence, dexterity, and efficiency of thinking and working children at the time. mature. Nutritional status refers to the state of the body caused by eating and using nutrients. This is due to maternity factors and poor parenting, especially the behavior and habits of children who do not eat according to their nutritional intake. Parental knowledge regarding a balanced and nutritious menu is the most influential factor in providing nutrition to toddlers. The lack of nutrition education by health workers makes mothers unable to prevent and overcome nutritional problems in their babies. Based on this, an application is needed that can facilitate parents, especially mothers, to control the nutritional status of their toddlers accompanied by nutritional guidelines for appropriate and balanced toddler food according to their age and nutritional adequacy. This research will build a mobile-based application in the form of a nutritional guide for toddlers' food that is appropriate and balanced according to their age and nutritional adequacy and a nutritional calculator for toddlers to control their nutritional status.